2016
DOI: 10.1111/jan.13036
|View full text |Cite
|
Sign up to set email alerts
|

Nurse safety outcomes: old problem, new solution – the differentiating roles of nurses’ psychological capital and managerial support

Abstract: Organizations are likely to benefit from upskilling nurses and their managers to increase nurses' psychological capital and managerial support, which then will enhance nurses' satisfaction with training and in-role safety performance perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Secondly, with reference to Brunetto et al. (), improvement of nurses’ perceived job‐related meaningfulness can be interpreted as a psychological resource for occupational stress prevention. In this regard, the present study provides evidence for nurses reporting high job‐related meaningfulness being more likely to engage in their job – benefiting from the buffering effect of meaningfulness on vulnerability to emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, with reference to Brunetto et al. (), improvement of nurses’ perceived job‐related meaningfulness can be interpreted as a psychological resource for occupational stress prevention. In this regard, the present study provides evidence for nurses reporting high job‐related meaningfulness being more likely to engage in their job – benefiting from the buffering effect of meaningfulness on vulnerability to emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of traditional public administration theory that underpins such policies and uses rationality and formal rules as the basis for explaining SLBs’ behaviour has been criticised for failing to capture the role and impact of emotions in their behaviour (Grimmelikhuijsen, Tummers, & Pandey, 2017; Vigoda‐Gadot & Meisler, 2010). If governments and organisations want innovative workers, then the policies must be based on empirical evidence that shows the impact on all stakeholders, including SLBs, because otherwise, irrespective of policy directives, the outcome is low level of employee wellbeing (Brunetto, Xerri, Farr‐Wharton et al, 2016, Xerri, Brunetto, & Farr‐Wharton, 2019), which likely results in limited innovative activity.…”
Section: Resultsmentioning
confidence: 99%
“…(2008) found that employees with high PsyCap were more likely to accept organisational change and those with low PsyCap required high levels of management support to be successful at work. Later, Brunetto, Xerri, Farr‐Wharton et al, (2016) found that nurses’ PsyCap, in addition to being associated with satisfaction with safety training, also predicted their safety behaviour in hospitals. Additionally, past research by Story, Youssef, Luthans, Barbuto, and Bovaird (2013) identified that LMX predicts the PsyCap of employees, although the quality of the LMX relationship was mediated by the frequency and quality of their communications.…”
Section: Introductionmentioning
confidence: 99%
“…The managerial support (MS) offered by the nurse manager offer is influenced by the quality of the workplace relationship that exist between nurses and nurse manager as alluded in the Social Exchange Theory (Brunetto, Xerri, Farr-Wharton, Shacklock, Farrwharton & Trinchero, 2016). The MS can either be instrumental which involves provision of job related information and feedback or provision of emotional support comprising empathy, caring, comfort and encouragement (Reblin & Uchino, 2008).…”
Section: Job Stressmentioning
confidence: 99%
“…Nurses may perceived their managerial as supportive based on how they help them during times of need, being praised for job well done, values their contribution and the care for their wellbeing (Edmondson & Boyer, 2013), feel more competent and valued (Pohl, Dal Santo, & Battistelli, 2013). Such perceptions impact on their organization performance, JS and staff turnover (Brunetto et al, 2016). Meta-analytical review of Edmondson and Boyer (2013) concluded existing of a significant positive correlation between MS and JS (Day, Crown & Ivany, 2017) effect on turnover and quality of patient care (Smollan, 2015).…”
Section: Job Stressmentioning
confidence: 99%